Analisis Konsep “Damai Sejahtera yang Melampaui Akal” dalam Filipi 4:6–7 sebagai Konsep Psikologis dalam Mengatasi Kecemasan - Disyon Arie Saldy Laja; Veronika Resta; Felix Munda (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Anxiety is one of the most prevalent psychological problems globally, yet approaches integrating spiritual dimensions remain underexplored. This study analyzes the concept of